Comparison of Outcomes of Live and Deceased Donor Renal Transplantation-A Retrospective Study from a single center in South India - Bharathi Kasinaboina; Swarnalatha Guditi; Gangadhar Taduri (Indian Journal of Kidney Diseases)
Background: Renal transplantation is the treatment modality of choice for patients with end-stage renal disease(ESRD). Living donors constitute the majority of the organ donor pool in India. Deceased donation program is only slowly evolving in the country. In this study, we aimed at comparing the outcome of live and deceased donor renal transplantation at our institute. Methods: This is a single-center, retrospective, observational study of renal transplant recipients from January 2010 to April 2016 conducted in a tertiary care centre in South India. The clinical profile, graft dysfunction, graft survival and patient survival rates of renal transplant recipients were analyzed. Results: Of 210 recipients, live donor renal transplant (LDRT) recipients were 176(83.80%) and deceased donor renal transplants (DDRT) were 34(16.19%). Delayed graft function was common in DDRT (64.7%) compared to LDRT (3.40%). Graft dysfunction episodes were commoner in DDRT (1.04 episodes/patient/year) compared to LDRT (0.43 episodes/patient/year). Higher rejection rate was seen in LDRT (25.56%) compared to DDRT (8.82%) with mean duration of follow up of 3.37± 1.80 years and 2.14 ± 1.12 years respectively. Modification of immunosuppression and noncompliance were the risk factors for rejection. Death censored graft survival rates at 6 months, 1 year and 5 years in LDRT were 98.9%, 97.2%, and 92.6% respectively and at 6 months, 1 year and 3.26 years in DDRT were 100%, 97%, and 94% respectively. Patient survival rates at 6 months, 1 and 5 years in LDRT were 94.3%, 91.5% and 86.4% respectively, and in DDRT patient survival rates at 6 months, 1 and 3.26 years were 91.2% 85.3% and 79.4% respectively. Though the patient survival rate was better in LDRT compared to DDRT, it did not reach statistical significance. Overall mortality rate was 14% and infection was the commonest (77.74%) cause of mortality. Mortality rates in LDRT and DDRT were 13.63% and 20.58% respectively. Conclusions: Live donors constitute the majority of the organ donor pool. DGF is commonly seen in DDRT. Rejection rate was higher in LDRT, with noncompliance and modification of immunosuppression being the risk factors. There is no difference in the patient and graft survival between LDRT and DDRT.